Conformationally Programmable Chiral Foldamers with Compact and Extended Domains Controlled by Monomer Structure. (12th June 2018) - Lockhart, Zachariah; Knipe, Peter C.
Abstract: Foldamers are an important class of abiotic macromolecules, with potential therapeutic applications in the disruption of protein–protein interactions. The majority adopt a single conformational motif such as a helix. A class of foldamer is now introduced where the choice of heterocycle within each monomer, coupled with a strong conformation‐determining dipole repulsion effect, allows both helical and extended conformations to be selected. Combining these monomers into hetero‐oligomers enables highly controlled exploration of conformational space and projection of side‐chains along multiple vectors. The foldamers were rapidly constructed via an iterative deprotection‐cross‐coupling sequence, and their solid‐ and solution‐phase conformations were analysed by X‐ray crystallography and NMR and CD spectroscopy. These molecules may find applications in protein surface recognition where the interface does not involve canonical peptide secondary structures. Abstract : Basteln nach Anleitung : Durch Verwendung isomerer heterocyclischer Verbindungsstücke konnte ein Foldamer erhalten werden, in dem über die Wahl des Monomers gezielt die Konformation des Makromoleküls vorgegeben werden kann – wie beim Bau einer Modellrennbahn aus Einzelteilen (siehe Bildhintergrund). Die Konformation ist das Ergebnis einer starken Dipolabstoßung; sie wurde durch Röntgen‐Strukturanalyse und 2D‐NMR‐Spektroskopie bestätigt.